2009
DOI: 10.1093/bjc/azp003
|View full text |Cite
|
Sign up to set email alerts
|

The Path and Promise of Fatherhood for Gang Members

Abstract: While an increase in research on criminal desistance has occurred in recent years, little research has been applied to the gang field. Using qualitative interview data, this article examines fatherhood as a potential turning point in the lives of 91 gang members in the San Francisco Bay Area. Fatherhood initiated important subjective and affective transformations that led to changes in outlook, priorities and future orientation. However, these subjective changes were not sufficient unless accompanied by two ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
86
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(96 citation statements)
references
References 40 publications
(51 reference statements)
6
86
0
1
Order By: Relevance
“…Despite arguments from criminological theory and evidence from qualitative studies that support a crime reducing effect of parenthood, particularly due to a new self-image and cognitive changes (Giordano, Cernkovich, & Rudolph, 2002;Moloney et al, 2009;Shannon & Abrams, 2007), quantitative results are best described as inconclusive. Whereas some studies have found a crime-reducing parenthood effect for men (Kerr et al, 2011;Savolainen, 2009;Zoutewelle-Terovan et al, 2014), other studies have found no effect (Blokland & Nieuwbeerta, 2005;Giordano et al, 2002;Monsbakken, Lyngstad, & Skardhamar, 2013;Warr, 1998) or even a crime-enhancing parenthood effect (Farrington & West, 1995).…”
Section: Desistance and Parenthoodmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite arguments from criminological theory and evidence from qualitative studies that support a crime reducing effect of parenthood, particularly due to a new self-image and cognitive changes (Giordano, Cernkovich, & Rudolph, 2002;Moloney et al, 2009;Shannon & Abrams, 2007), quantitative results are best described as inconclusive. Whereas some studies have found a crime-reducing parenthood effect for men (Kerr et al, 2011;Savolainen, 2009;Zoutewelle-Terovan et al, 2014), other studies have found no effect (Blokland & Nieuwbeerta, 2005;Giordano et al, 2002;Monsbakken, Lyngstad, & Skardhamar, 2013;Warr, 1998) or even a crime-enhancing parenthood effect (Farrington & West, 1995).…”
Section: Desistance and Parenthoodmentioning
confidence: 99%
“…Male offenders who are asked about their fertility intentions often state that they feel not fit to be a parent in terms of finances or lifestyle (Buston et al, 2010;Moloney et al, 2009;Shannon & Abrams, 2007;Wilkinson et al, 2009). There is a continued ideal of a stable relationship and a good job providing M a n u s c r i p t 5 financial security before having children.…”
Section: Parenthood Intentions Of High-risk Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, evidence shows that it is the effect of social controls that urge people to stop offending. For instance, gang members leave the gang in favor of fatherhood (Moloney, Mackenzie, Hunt & Joe-Laidler, 2009) and employment, military service and marriage all contribute to a cessation of offending (Sampson & Laub, 2001). It therefore seems that social controls may be more flexible than control theory suggests and that even if informal social controls break down to the extent that youth become involved in delinquency, they maintain influence during the period of delinquency and can be re-established sufficiently to facilitate desistance.…”
Section: Control Theory: Empirical Evidencementioning
confidence: 99%
“…Maruna, LeBel, and Lanier (2003) reported that close family attachments give prisoners some sense of direction and meaning in their lives, bringing up children being incompatible with imprisonment (Edin, Nelson, and Parnal 2001;Moloney et al 2009). …”
Section: Initiatives Around Children's Literacy For Imprisoned Fathersmentioning
confidence: 99%